2017
DOI: 10.1016/j.celrep.2017.11.091
|View full text |Cite
|
Sign up to set email alerts
|

SRSF1 Prevents DNA Damage and Promotes Tumorigenesis through Regulation of DBF4B Pre-mRNA Splicing

Abstract: Dysregulated alternative splicing events have been implicated in many types of cancer, but the underlying molecular mechanisms remain unclear. Here, we observe that the splicing factor SRSF1 regulates DBF4B exon6 splicing by specifically binding and promoting its inclusion. Knockdown of the exon6-containing isoform (DBF4B-FL) significantly inhibits the tumorigenic potential of colon cancer cells in vitro and in mice, and SRSF1 inactivation phenocopies DBF4B-FL depletion. DBF4B-FL and SRSF1 are required for can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 23 publications
1
50
0
Order By: Relevance
“…The maintenance of genomic stability is of paramount importance to living organisms including cancer cells; thus, many proteins including splicing factors and RNA surveillance factors have been known to participate in DNA damage response . Our studies have identified that CHERP/SR140 and UPF3A are novel players involved in DNA damage response, as loss of them leads to DSB and triggers spontaneous DNA damage response and cell death.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…The maintenance of genomic stability is of paramount importance to living organisms including cancer cells; thus, many proteins including splicing factors and RNA surveillance factors have been known to participate in DNA damage response . Our studies have identified that CHERP/SR140 and UPF3A are novel players involved in DNA damage response, as loss of them leads to DSB and triggers spontaneous DNA damage response and cell death.…”
Section: Discussionmentioning
confidence: 79%
“…Levels of splicing factors such as SRSF1, SRSF6, SRSF10, hnRNPK or hnRNPLL are significantly altered in many types of cancer including CRC . Therefore, it is not surprising that dysregulated AS events can contribute to almost all hallmarks of cancer, including sustained proliferation and evasion of apoptosis .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations